The Social Subject in the Context of Modern Concepts of the Other - I. Palahuta, Vadym; Blikhar, Viacheslav; KASHCHUK, MARIANA (Beytulhikme, 2024)
Purpose. The study is dedicated to the analysis of structuralist and poststructuralist concepts of the Other (Others) as the basis for the formation of social subjectivity and the subject's identity. Theoretical basis. The authors proceed from the assumption that the conceptualization of the Other of traditional philosophical structuralism with his absolutization of the "process without a subject" imposes from the outside, sometimes unacceptable and alien to the subject identity. Scientific novelty. The authors prove the need for further research into multivariate concepts of the Other, which testify to a fairly complex process of subjectivation in the present, which takes place on an uncontrolled, unconscious level. Conclusions. The authors identified directions for further study of the problem of transformation and incorporation of concepts of the Other into modern social structures, which significantly modify the content and role of collective identity in the process of subjectivation of individuals, which becomes a promising topic for future research.